Cellular properties and chemosensory responses of the human carotid body. (25th November 2013) - Ortega‐Sáenz, Patricia; Pardal, Ricardo; Levitsky, Konstantin; Villadiego, Javier; Muñoz‐Manchado, Ana Belén; Durán, Rocío; Bonilla‐Henao, Victoria; Arias‐Mayenco, Ignacio; Sobrino, Verónica; Ordóñez, Antonio; Oliver, María; Toledo‐Aral, Juan José; et al.
Key points The carotid body (CB) is a key chemoreceptor organ that mediates the hyperventilatory response to hypoxia, and contributes to the process of acclimatisation to chronic hypoxaemia. Knowledge of CB physiology at the cellular and molecular levels has advanced considerably in recent times thanks to studies on lower mammals; however, information on humans is practically absent. Here we describe the properties of human CB cells in slice preparations or after enzymatic dispersion. Besides glomus (type I) and glia‐like, sustentacular (type II) cells, adult human CBs contain nestin‐positive neural progenitor cells. The human CB also expresses high levels of glial cell line‐derived neurotrophic factor. These properties are maintained at an advanced age. Human glomus cells contain a relatively high density of voltage‐dependent Na+, Ca2+ and K+ channels. Membrane depolarisation with high extracellular K+ induces an increase of cytosolic [Ca2+] and quantal catecholamine release. Human glomus cells are responsive to hypoxia and hypoglycaemia, both of which induce an increase in cytosolic [Ca2+] and transmitter release. Chemosensory responses of glomus cells are also preserved at an advanced age. These findings on the cellular and molecular physiology of the CB provide novel perspectives for the systematic study of pathologies involving this organ in humans. Abstract The carotid body (CB) is the major peripheral arterial chemoreceptor in mammals that mediates the acute hyperventilatory response to hypoxia. The CB grows in response to sustained hypoxia and also participates in acclimatisation to chronic hypoxaemia. Knowledge of CB physiology at the cellular level has increased considerably in recent times thanks to studies performed on lower mammals, and rodents in particular. However, the functional characteristics of human CB cells remain practically unknown. Herein, we use tissue slices or enzymatically dispersed cells to determine the characteristics of human CB cells. The adult human CB parenchyma contains clusters of chemosensitive glomus (type I) and sustentacular (type II) cells as well as nestin‐positive progenitor cells. This organ also expresses high levels of the dopaminotrophic glial cell line‐derived neurotrophic factor (GDNF). We found that GDNF production and the number of progenitor and glomus cells were preserved in the CBs of human subjects of advanced age. Moreover, glomus cells exhibited voltage‐dependent Na+, Ca2+ and K+ currents that were qualitatively similar to those reported in lower mammals. These cells responded to hypoxia with an external Ca2+‐dependent increase of cytosolic Ca2+ and quantal catecholamine secretion, as reported for other mammalian species. Interestingly, human glomus cells are also responsive to hypoglycaemia and together these two stimuli can potentiate each other's effects. The chemosensory responses of glomus cells are also preserved at an advanced age. These new data on the cellular and molecular physiology of the CB pave the way for future pathophysiological studies involving this organ in humans.